2020
DOI: 10.1126/science.abb6430
|View full text |Cite
|
Sign up to set email alerts
|

The mouse Sry locus harbors a cryptic exon that is essential for male sex determination

Abstract: The mammalian sex-determining gene Sry induces male development. Since its discovery 30 years ago, Sry has been believed to be a single-exon gene. Here, we identified a cryptic second exon of mouse Sry and a corresponding two-exon type Sry (Sry-T) transcript. XY mice lacking Sry-T were sex-reversed, and ectopic expression of Sry-T in XX mice induced male development. Sry-T messenger RNA is expressed similarly to that of canonical single-exon type Sry (Sry-S), but SRY-T protein is expressed predominantly becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 24 publications
0
44
0
1
Order By: Relevance
“…Data were mapped to the mouse reference genome GRCm38.p5 in which the eGFP (NC_011521.1) combined with the bovine GH 3’-splice/polyadenylation signals ( 39 ) (NM_180996.1) sequences have been added. It has recently been established that the mouse Sry locus harbors a cryptic exon that is essential for male sex determination ( 63 ). As this exon is located in a palindromic region, all reads mapping to this region are also mapping to the positive strand and discarded as multimappers.…”
Section: Methodsmentioning
confidence: 99%
“…Data were mapped to the mouse reference genome GRCm38.p5 in which the eGFP (NC_011521.1) combined with the bovine GH 3’-splice/polyadenylation signals ( 39 ) (NM_180996.1) sequences have been added. It has recently been established that the mouse Sry locus harbors a cryptic exon that is essential for male sex determination ( 63 ). As this exon is located in a palindromic region, all reads mapping to this region are also mapping to the positive strand and discarded as multimappers.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, Sry itself was not called in our scRNA-seq data. Recently, however, it was reported that Sry has an additional exon downstream of the classical exon ( Miyawaki et al., 2020 ). Indeed, our scRNA-seq detected many reads from exon 2 ( Figure S6 A).…”
Section: Resultsmentioning
confidence: 99%
“…The gene regulatory network of male and female SD- and developmental pathways are best-studied in laboratory house mice [ 7 ]. While for 30 years Sry has been thought to comprise a single exon, a cryptic second exon, essential for male SD in mice has just been identified [ 337 ]. Although eutherian XX/XY sex determination is extremely conserved, a few rodent species evolved unusual, derived sex chromosome systems [ 338 ].…”
Section: Overview Of Current Knowledge About Sex Evolution Across the Vertebrate Phylogenymentioning
confidence: 99%